Negotiating the edge : resolving the conflicts and potentials between endogenous and exogenous environments in peri-urban settlement by creating a condition for a narrative between the two extremes - Van Rooyen, Neels (University of Pretoria, 2015)
Dissertation (MArch(Prof))--University of Pretoria, 2014.